Entrepreneurial Intentions of Female Students: Exploring Entrepreneurial Feasibility and Desirability through Personality Traits - Abin John; Vanitha Selvaraj; Muhammed Jisham (Colombo Business Journal)
Women’s entrepreneurship drives economic growth and social transformation. This study integrates personality traits into the entrepreneurial event model to assess entrepreneurial intentions, identifying specific personality traits as antecedents of perceived desirability and feasibility, two core components of the entrepreneurial event model. Data from 382 final-year commerce and management students were analysed using partial least squares structural equation modelling. The results show traits like innovativeness, entrepreneurial alertness, and the need for achievement shape perceived desirability. Further, perceived feasibility is influenced by risk-taking motives, proactiveness, and an internal locus of control. Finally, positive relationships were identified between perceived desirability and feasibility with entrepreneurial intentions. This research underscores the importance of personality traits as antecedents of perceived desirability and feasibility, providing insights for promoting entrepreneurship among female commerce and management students. It has implications for policy and educational initiatives to provide targeted support to students with these personality traits to foster female entrepreneurship.